Akibat Hukum terhadap Tindak Pidana Perjudian Balap Liar di Kota Denpasar - Gede Indra Yasa Asiawan; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Jurnal Konstruksi Hukum, 2020)
Every citizen has different characteristics and desires every day including Indonesian citizens from young people to old ones have varied ambitions in life and action. The behavior of each individual in order to achieve various goals, either hobbies or ways of living life which is also limited by government regulations that require a person to obey the current positive laws. This research discusses how the regulation of gambling of illegal racing in Denpasar City and how the effect of consequences of gambling of illegal racing in Denpasar City. The method used in this research is a type of normative legal research which is carried out by the method of recording and reviewing legal materials. The results of this study indicate that the regulation of criminal acts committed by adolescents in illegal racing has not been regulated in certain regulations, but the acts committed by these teenagers have violated the provision of Law No. 22 of 2009, while the final result of the sanctions imposed by the police on gambling of illegal racing is not very effective, because the sanctions are only in the form of warnings and then called by their respective parents, if they are caught doing it again or someone is still doing it and gets the same act then their vehicle is ticketed or detained. As for preventive legal protection regarding prevention, it has been carried out not only from the police, but from the community, village heads or village officials and especially parents whose children are involved in this group, who contribute more in overcoming and preventing future actions that breaks the law.